2018
DOI: 10.3390/brainsci8080150
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Neural Basis of Cognitive Behavioral Therapy in Psychiatric Disorders: A Focus on Depression

Abstract: Background: Major depressive disorder (MDD) stands among the most frequent psychiatric disorders. Cognitive behavioral therapy (CBT) has been shown to be effective for treating depression, yet its neural mechanisms of action are not well elucidated. The objective of this work is to assess the available neuroimaging studies exploring CBT’s effects in adult patients with MDD. Methods: Computerized databases were consulted till April 2018 and a research was conducted according to PRISMA guidelines in order to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 78 publications
1
12
0
1
Order By: Relevance
“…We observed greater differences between ICBT and the other two methods, particularly on week 18, where ICBT exhibited notable efficacy regarding anxiety and depression. Our study results are in accordance with previous published data [47,48]. Findings from a recent meta-analysis examining the neural basis of CBT, and its effects on symptoms of anxiety and depression, showed that CBT exerts its effects on anxiety and depression by enhancing the top–down cognitive control of emotions (e.g., prefrontal regions) and/or decreasing the bottom–up flow of fear-related emotions from limbic structures [49].…”
Section: Discussionsupporting
confidence: 94%
“…We observed greater differences between ICBT and the other two methods, particularly on week 18, where ICBT exhibited notable efficacy regarding anxiety and depression. Our study results are in accordance with previous published data [47,48]. Findings from a recent meta-analysis examining the neural basis of CBT, and its effects on symptoms of anxiety and depression, showed that CBT exerts its effects on anxiety and depression by enhancing the top–down cognitive control of emotions (e.g., prefrontal regions) and/or decreasing the bottom–up flow of fear-related emotions from limbic structures [49].…”
Section: Discussionsupporting
confidence: 94%
“…El proceso puede ser internalizado luego de un breve periodo de tiempo, pero requerirá de práctica y repetición para aumentar su eficacia [38].…”
Section: Procesamiento Cognitivo-afectivo Asimétrico Y Reestructuraciunclassified
“…A discrepancy exists among the available studies regarding the type of psychotherapy intervention, the number of psychotherapy and NIBS sessions, the pharmacological profiles of treated patients, the presence of psychiatric comorbidities and the presence of a sham intervention. All the reported studies applied NIBS techniques over the PFC, a region that was previously found to have an enhanced activity or an increase in its functional connectivity with other areas (fronto-limbic connections) following psychotherapy [3,36]. Therefore, tDCS and rTMS may have acted by enhancing CBT effects on the top-down cognitive control of emotion.…”
Section: Current Knowledge and Future Perspectivesmentioning
confidence: 99%